Исследование мощности электромагнитных модуляторов вибраций - Божко, А. Е.; Иванов, Е. М.; Иванова, З. А.; Мягкохлеб, К. Б. (НТУ "ХПИ", 2014)
В данной работе осуществляется попытка более детально определить энергетические показатели электромагнитных вибровозбудителей, находящих широкое применение в технологических процессах уплотнения сред, для передвижения в конвейерах материалов, в испытательных стендах и т.д. Энергетические показатели определяются с учетом вибрационного движения массы и потерь, возникающих в электрической и механической частях. Эти результаты необходимы для оптимального выбора управляющего устройства по энергетическим показателям.

Electromagnetic vibroexciters find wide adaptation in technological processes of condensation of environments, for movement in conveyors of materials, in test beds, etc. In each case loading is the weight which can be located on mobile parts (rotor) electromagnetic exciters directly, or through elastic elements (springs). For formation of movement of anrotor in the form of weights vibration it is necessary to know power parameters electromagnetic vibroexciter. The detailed analysis and a conclusion of power correlation taking into account of mechanical loadings and frequencies of mobile system electromagnetic exciters vibrations are absent, though some brief data about power electromagnetic exciters in the literature are available. In this paper an attempt is made to further define the energy indicators of electromagnetic exciters with regard to the vibratory motion of the mass and losses arising in electrical and mechanical parts.
An investigation of the power of the electromagnetic modulator of vibrations
Keywords: якорь; зазор воздушный; демпфирование; жесткость; система колебательная; anchor; air gap; damping; rigidity; oscillatory system